(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The use of Information and Communication Technology (ICT) as a tool to improve the teaching of English in Indian schools has garnered much attention and investment recently. However, with teacher professional development dominated by crash courses and one-off ICT workshops, teachers will seldom change their teaching practices to improve their students’ knowledge and understanding. Investigations claim that teachers do not transmit the knowledge and skills they learn in professional development, characterised by formal face-to-face training sessions, to classroom teaching practices without continuous follow-up, peer discussions and teacher teamwork.Integrating Information and Communication Technology (ICT) into teaching and learning is a growing area that has attracted many educators’ attention in recent years. Teachers need to be involved in collaborative projects and development of intervention change strategies, which in-clude teaching partnerships with ICT as a tool. Teacher perceptions are a major predictor of the use of new technologies in instructional settings. Early studies have indicated that blended learn-ing can be as successful as either online or face-to-face instruction, particularly in teacher prepa-ration programs.